2008
DOI: 10.1021/ja8042382
|View full text |Cite
|
Sign up to set email alerts
|

A Heterobimetallic Complex With an Unsupported Uranium(III)−Aluminum(I) Bond: (CpSiMe3)3U−AlCp* (Cp* = C5Me5)

Abstract: The discovery of molecular metal-metal bonds has been of fundamental importance to the understanding of chemical bonding.1 For the actinides, examples of unsupported metalmetal bonds are relatively uncommon, consisting of Cp 3 USnPh 3 , and several actinide-transition metal complexes. Traditionally, bonding in the f-elements has been described as electrostatic; however, elucidating the degree of covalency is a subject of recent research. 3 In carbon monoxide complexes of the trivalent uranium metallocenes, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
84
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 35 publications
(28 reference statements)
0
84
1
2
Order By: Relevance
“…It was therefore proposed that the lower magnetic moment of 59 was due to the cationic nature of 59 resulting in a shorter uranium-iron distance and better orbital overlap. (60), which was isolated as dark brown crystals from cold (K808C) pentane (Minasian et al 2008). An X-ray diffraction study revealed an unsupported uranium-aluminium bond with a uranium-aluminium bond distance of 3.117(3) Å, which is within the sum of the covalent radii of uranium and aluminium (3.17 Å) (Cordero et al 2008).…”
Section: Ln Sn Snmentioning
confidence: 99%
“…It was therefore proposed that the lower magnetic moment of 59 was due to the cationic nature of 59 resulting in a shorter uranium-iron distance and better orbital overlap. (60), which was isolated as dark brown crystals from cold (K808C) pentane (Minasian et al 2008). An X-ray diffraction study revealed an unsupported uranium-aluminium bond with a uranium-aluminium bond distance of 3.117(3) Å, which is within the sum of the covalent radii of uranium and aluminium (3.17 Å) (Cordero et al 2008).…”
Section: Ln Sn Snmentioning
confidence: 99%
“…[2] Much work has been done elucidating the bonding properties of similar d/f-block compounds of the general formula…”
mentioning
confidence: 99%
“…These data are quite comparable to the Ru À Ga distances in related RuÀGaCp* complexes and clusters. [14,15] Following usual electron-counting rules, 1 can be viewed as being formally composed of the unsaturated neutral 16 electron fragment {(GaCp*) 3 (H) 2 Ru II } and the saturated neutral 18 electron fragment {(GaCp*) 4 . [9] Note, that the Pt dimer [Pt 2 H(Ga)-(GaCp*) 7 ] 2+ is isoelectronic to 1 (a total of 34 valence electrons for both M 2 Ga 8 core structures).…”
mentioning
confidence: 99%
“…[1] Ein jüngeres Glanzlicht ist der Komplex [h 5 -{(Me 3 Si)C 5 H 4 } 3 U(AlCp*)] mit der ersten freien ActinoidAluminium-Bindung. [2] Viel Arbeit wurde in die Untersuchung der Bindungseigenschaften von ähnlichen d-f-BlockVerbindungen der allgemeinen Formel [L a M b (ER) c ] investiert, [3] während über ihre metallorganischen Reaktionen und die damit verbundenen Anwendungsmöglichkeiten deutlich weniger berichtet wurde. Die homoleptischen Verbindungen [M a (ECp*) b ] sind wegen der flexiblen Bindungseigenschaften der Cp*-Gruppen am Gruppe-13-Metallatom von besonderem Interesse.…”
unclassified
“…Diese Daten entsprechen den Ru-Ga-Abständen verwandter Ru-GaCp*-Komplexe und -Cluster. [14,15] Unter Verwendung üblicher Elektronenzählregeln (mit dem 2e-Donorligand H À und dem "nackten" Ga-Ligand als 0e-Donor Ga + ) setzt sich 1 formell zusammen aus einem ungesättigten neutralen 16e-Fragment {(GaCp*) 3 (H) 2 Ru II } und einem gesättigten 18e-Fragment {(GaCp*) 4 (H)Ru 0 (Ga)}. Die lineare Ru-Ga-Ru-Anordnung von 1 begründet sich durch die starken s-und p-Akzeptoreigenschaften von "nacktem" Ga…”
unclassified